Association of TLR7 and MyD88 Gene Polymorphism with Trichomoniasis vaginalis Infection - Kermasha, Zainab Waddah; Al-Masoudi, Hayam Khalis; Al-Shaikh, Suhaila Fadhil (Journal of Contemporary Medical Sciences, 2023)
Objective: Toll-like receptor 7 (TLR7) and MyD88 represent important components of the innate immune response which play a crucial role in recognition of T. vaginalis. Single nucleotide polymorphisms (SNPs) in TLRs and MyD88 were manifested as key determinant affecting the susceptibility to trichomoniasis. This study aims to examine the impact of two SNPs, designated rs179008 and rs4988453 in TLR7 and MyD88, respectively, on Iraqi women infected with T. vaginalis. Methods: Women vaginal swabs as well as blood samples were collected from 186 female patients diagnosed clinically by gynecologists. These pateints were admitting the gynecology clinics in three public hospitals in Babel governorate in Iraq. Clinical samples were obtained for molecular identification of the parasite, sequencing of the TLR7 and MyD88 genes as well as performing the corresponding immunological studies. Results: The PCR assays showed 40 positive women (95% CI, 15.85 to 28.11) of T. vaginalis β-tubulin gene. Genetic studies of rs179008 SNP in TLR7 showed that the mutant T allele revealed significantly more prevalence in women infected with T. vaginalis in comparison with controls (p<0.001), furthermore, AT and TT genotypes distribution were significantly greater in patients than that in controls (p<0.01). Moreover, genetic analysis of rs4988453 SNP in MyD88 demonstrated that the mutant A allele almost has close frequency between patients and controls, and the heterozygous CA and homozygous AA genotypes were almost normally distributed between controls and patients. Finally, the concentrations of TLR7 and MyD88 were significantly elevated in the majority of women patients aged between 16-40 years. Conclusion: The mutant allele A of rs4988453 SNP in MyD88 did not show an association with increased risk of trichomonas infection, however, the mutant allele T of rs179008 SNP in TLR7 might make women more sensitive for infection with T. vaginalis. However, more studies are needed to confirm these findings and to understand the underlying involved mechanisms.